CRIGOS a compact robot for image-guided orthopedic surgery. - Brandt, G. (IEEE Transactions on information technology in biomedicine)
The CRIGOS (compact robot for image-guided orthopedic surgery) project was set up for the development of a compact surgical robot system for image-guided orthopedic surgery based on user requirements. The modular system comprises a compact parallel robot and a software system for planning of surgical interventions and for supervision of the robotic device. Because it is not sufficient to consider only technical aspects in order to improve clinical routines the therapeutic outcome of conventional interventions, a user-centered and task-oriented design process has been developed which also takes human factors into account. The design process for the CRIGOS system was started from requirement analysis of various orthopedic interventions using information gathered from literature, questionnaires, and workshops with domain experts. This resulted in identification of conventional interventions for which the robotic system would improve the medical and procedural quality. A system design concept has been elaborated which includes definitions of components, functionalities, and interfaces, Approaches to the acquisition of calibrated X-rays will be presented in the paper together with design and evaluation of a first human-computer interface. Finally, the first lab-type parallel robot based on low-cost standard components is presented together with the first evaluation results concerning positioning accuracy.